Socioeconomic risk factors of hypertension and blood pressure among persons aged 15–49 in Nepal: a cross-sectional study - Sushant Joshi; Bishnu Bahadur Thapa (BMJ Open)
Objectives This study estimated the prevalence of hypertension, in accordance with the American College of Cardiology and American Heart Association’s 2017 guidelines, and examined the association between various socioeconomic factors and systolic blood pressure (SBP), diastolic blood pressure (DBP) and hypertension.Setting and design We used nationally representative data from the 2016 Nepal Demographic and Health Survey. Multivariate analysis was used to study the association of hypertension with socioeconomic factors: logistic regression was used for hypertension and linear regression was used for DBP and SBP.Participants Our sample consisted of 9827 adults between the ages of 15 and 49 years.Results The prevalence of hypertension was 36%. The mean DBP and SBP were 76.4 and 111.5, respectively. Janjatis (adjusted OR (AOR): 1.34, CI: 1.12 to 1.59), Other Terai castes (AOR: 1.38, CI: 1.03 to 1.84), Muslim and other ethnicities (AOR: 1.64, CI: 1.15 to 2.33) and Dalits (AOR: 1.26, CI: 1.00 to 1.58) had higher odds of hypertension. Individuals employed in professional, technical and managerial professions collectively (AOR: 1.62; CI: 1.18 to 2.21) also had higher odds of hypertension. Moderately food insecure household had lower odds of hypertension (AOR: 0.84; CI: 0.72 to 0.99) compared with households with no issue of food insecurity. Results were similar for SBP and DBP. When stratified by sex, there were differences mainly in terms of occupation and ethnicity.Conclusion There are substantial disparities in hypertension prevalence in Nepal. These disparities extend across ethnic groups, occupational status and food security status. Differences also persist across different provinces. As hypertension continues to be increasingly more significant, more research is needed to better understand the disparities and gradients that exist across various socioeconomic factors.